An Anthropology of Learning On Nested Frictions in Cultural Ecologies - Hasse, Cathrine; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2015)
This book deals with the black box of social science methodology: participant observation. From the perspective of anthropology, it explores the difference between an ethnographer as participant observer and any other participant. It discusses and gives insight into what participant observers do before they write their texts. It explains how they learn to engage with other people$1 (Bs cultural ecologies and develop relational expertise. Showing that anthropology is a craft of cultural learning processes, the book introduces the engaged participant observer as an expert ethnographer capable of aligning engagements with others. It argues that culture as representation is replaced by culture as a frictioned learning process through which collective and social cultures emerge. To advance understanding of the ethnographer$1 (Bs learning process, the book introduces a new methodological vocabulary of cultural learning processes that is based on a diffracted reading of ethnography, anthropological theory, post-phenomenology, feminist materialism and cultural-historical activity theory.s
Foreword -- 1. Introducing the engaged anthropologist -- 2. Culture as contested field -- 3. Collective and social cultures -- 4. Position matters! -- 5. Social designations of cultural markers -- 6. Learning from culture contrast -- 7. Towards nested engagement -- 8. Future zones of development -- 9. Epilogue. Index.
Keywords: Education; Anthropology; Education; Learning & Instruction; Anthropology; Professional & Vocational Education; Electronic books